Sufism-Based Multicultural Education for The Peace of Indonesia - Hadarah, Hadarah; Soleha, Soleha (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Sufism-based multicultural education seems to be new, yet substantially not. Partially, the models or designs which combine two important elements have actually developed in Indonesia. Sufism-based attitudes have become interesting phenomena related to the life of the diverse and heterogeneous Indonesian people as well as the constructions of various tribes, ethnics, and religions in forming the multicultural communities. Sufism values may become an underlying frame of each religion. This article reveals the facts found in the sociological qualitative research results showing that Malay-Bangka Islamic Sufi tend to build more dominant multicultural community in adjacent with the Chinese community of which population is bigger than the Moslem community, as well as with Christian, Hindu, and Buddha communities to live peacefully and respect each other. The problem is that Sufism-based multicultural education as a new education model for the peace of Indonesia has not been successfully made as well as its implementation in learning curriculum gradually based on the capacity of elementary to higher education students to draw the government‟s attention. The democratic movements highly demand on the acknowledgement of diversity in the body of Indonesia which has various tribes, ethnics, beliefs, and religions. Designing a new education model is one alternative to maintain and gather various cultures of the nation‟s communities to the globalization era as well as to fundamentally cultivate the values, starting from the level of primary to higher education students and develop the attitudes to respect and understand each other. In this case, Sufism-based multicultural education is one accommodative alternative education model to overcome various problems in heterogeneous communities